Empire and Identity in Guizhou Local Resistance to Qing Expansion - Weinstein, Jodi L. (University of Washington Press, 2013)
This historical investigation describes the Qing imperial authorities attempts to consolidate control over the Zhongjia, a non-Han population, in eighteenth-century Guizhou, a poor, remote, and environmentally harsh province in Southwest China. Far from submitting peaceably to the states quest for hegemony, the locals clung steadfastly to livelihood choiceschiefly illegal activities such as robbery, raiding, and banditrythat had played an integral role in their cultural and economic survival. Using archival materials, indigenous folk narratives, and ethnographic research, Jodi Weinstein shows how these seemingly subordinate populations challenged state power.